Analisis Pendokumentasian Catatan Kesehatan Ibu Hamil Pada Buku Kesehatan Ibu Dan Anak (Kia) Dipuskesmas KartasuraTahun 2016 - Siswiantari, Cahya Novita; , Sri Sugiarsi, SKM., M.Kes; , Anisa Catur W, SKM., M.Epid (2016)
Books Maternal and Child Health (MCH) is a means of recording evidence of maternal and child health services thoroughly and continuously held by the mother or family. Maternal and child health services including immunization, as well as records of disease and developmental problems must be recorded completely and correctly. Because the recording of the MCH handbook used as monitor the health of mothers and children, including early detection of maternal and child health issues. The purpose of this study to analyze the documentation Notes Maternal Health at MCH handbook in Puskesmas. This type of research is a combination of quantitative and qualitative research (mixed methodology). The population in this study guide KIA with a total sample of 51 books KIA. The informants are four midwives and two pregnant women. The research data is the implementation documentation of medical records of pregnant women at health centers KIA book Kartasura. Analysis of the research conducted by quantitative and qualitative methods.The results showed Anamnesa unfilled sheet of 19 books KIA ( 37.26 ) , physical examination unfilled sheet of 16 books KIA ( 31.37 % ) , incompleteness caused by impatient midwives factor in documentation and factors of pregnant women who do not bring a book while visiting . Implementation of a book documenting the KIA in Puskesmas Kartasura are in accordance with Antenatalcare services according to the MOH ( 2004) . But still encountered in the documentation of incompleteness